The fulfillment of standards on child cares (Taman Penitipan Anak (TPA) and Taman Anak Sejahtera (TAS)) for the quality improvement of alternative care with the child protection perspective - Rita Pranawati; Naswardi Naswardi; Sander Diki Zulkarnaen (Universitas Negeri Yogyakarta, 2021)
The increasing need for child care in the industrialization era as alternative care on both Taman Penitipan Anak (TPA) and Taman Anak Sejahtera (TAS) match the quality and child protection perspective. This study measures the quality of child care from three aspects, namely institutional, human resources, and service programs. This study uses a quantitative method, applying questionnaires interviewed and data processed using SPSS. The samples of this study are TPA and TAS in 9 provinces representing the diversity. The study found that about 44% of child care do not have a license which will affect services. The staffs have adequate quality but it is necessary to hold a selection process ensuring the child protection perspective and a good track record. Training is necessary to improve the knowledge and skills related to child protection and development. There is still 20% of child care that needs to improve the quality.